Analyzing the Effect of Cargo Handling on the Respective Workload and Balancing of Scheduled Logistics Flight in Metro Manila - Edgardo O. Bocalbos; Quio P. Dollano; Sharmaine Mae R. Ellera; Lian Joachim N. Licudine; James Brian N. Añola; Luzcel B. Gonzales; Angel A. Angeles; Jeremy Peter T. Sablayan; Marianne Shalimar G. Del Rosario (International Journal of Progressive Research in Science and Engineering, 2025)
This study explores the impact of cargo handling on workload distribution and logistics flight scheduling in Metro Manila, focusing on processes like loading, unloading, and transit times. These factors influence flight punctuality, crew workload, and operational efficiency. A mixed-methods approach combined quantitative surveys with qualitative interviews to capture the personal experiences of cargo handlers, highlighting issues like work-life balance and mental health. Key findings include differences in physical strength and stamina between men and women, affecting task assignments in high-pressure environments. The study also reveals distinct gender-based coping strategies, with men favoring food consumption and teamwork as stress relief methods. These gender dynamics raise questions about task allocation, inclusion, and team collaboration in logistics. Data analysis used cross-tabulation, thematic analysis, and statistical tests to validate findings and examine gender’s influence on teamwork and stress management. The research offers recommendations for optimizing cargo handling practices, enhancing job satisfaction, and promoting a healthy work environment. It emphasizes ethical research standards, aiming to guide industry professionals and policymakers while laying the groundwork for future global studies on cargo logistics.